Design and Synthesis of a Ferrocene‐Based Diol Library and Application in the Hetero‐Diels‐Alder Reaction. Issue 6 (8th December 2022) - Cunningham, Laura; Guiry, Patrick J.
Abstract: Diol scaffolds have been utilized as highly effective catalysts and ligands in a wide range of catalytic asymmetric transformations. For scaffolds to be successful as broadly used motifs, they should be prepared cheaply through facile routes and be easily handled. Herein, the synthesis of a family of planar chiral diols based on a modular and robust three‐step route is described, which yields catalytically active diols in >99 % de and >99 % ee, with up to seven different chiral elements. These diols have been characterized by X‐ray crystallographic analysis, which provides clear evidence for the likely transition state when applied in the asymmetric hetero‐Diels‐Alder reaction. Without altering the stereochemistry of the catalyst backbone, it is possible to access both enantiomers of the product by varying the substitution of the catalyst at the α‐position. Abstract : The development of a library of ferrocenyl diols, establishing a fundamental structure–activity relationship through a modular three‐to‐four‐step synthesis is described. These diols are prepared with complete enantio‐ and diastereoselectivity across seven chiral elements (2 planes, 2 centres, and 3 axes) and are catalytically active in the hetero‐Diels–Alder reaction. Characterization by X‐ray crystallography shows intricate inter‐ and intramolecular hydrogen bonding, as well as uncommon bifurcated hydrogen bonding.